Effects of sex steroids on spatial cognition in the zebra finch (Taeniopygia guttata) - Haggis, Olivia (The University of Edinburgh, 2010)
It is well established in mammals that chronic, long-term elevations in sex steroids are associated with improvements in spatial cognition. It is less clear the extent to which short to medium term elevations in sex steroids improve spatial cognition and change hippocampal morphology, particularly in birds. The avian hippocampus expresses both androgen receptors (AR) and oestrogen receptor alpha (ERα) and high levels of the enzyme aromatase that converts testosterone to oestrogen. I began by comparing spatial cognition, hippocampal sex steroid receptor and aromatase expression between males and females. There were no differences in spatial or visual cognition or in hippocampal sex steroid receptor expression between the sexes, although hippocampal aromatase mRNA expression was higher in males. I then addressed the effects of acute and medium-term sex steroid treatment on spatial cognition and hippocampal aromatase and sex steroid receptor expression. A single treatment of testosterone 30 minutes or four hours prior to cognitive testing improved spatial performance. Additionally, when testosterone and oestrogen were given daily for five days spatial cognition in both sexes was improved. The testosterone-induced improvement was blocked when testosterone was administered in conjunction with the aromatase inhibitor fadrozole but not when administered with saline. These findings suggest that spatial cognition is improved by an oestrogenic effect. Thirty minutes following acute testosterone treatment, plasma testosterone levels, hippocampal AR and ERα mRNA expression all increased. Five days of oestrogen treatment increased plasma oestrogen levels, hippocampal ERα mRNA and Nmethyl- D-aspartate (NMDA) receptor levels in males and females; all were positively correlated with enhanced spatial cognition on day five of treatment. Finally, I determined which genes were differentially expressed as a result of five days of oestrogen treatment. Nineteen genes, identified as being involved in learning and memory were differentially expressed in the hippocampus, eleven of which were up-regulated and eight were down-regulated. Taken together these results demonstrate that oestrogen can improve spatial cognition in birds. It is plausible that oestrogen acts to improve spatial memory in the hippocampus through upregulation of genes that control neurotransmitter release, reuptake and receptor levels.
Keywords: zebra finch; spatial cognition; steroids, sex; avian hippocampus; oestrogenic effect